Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma: A Review of the Literature with Updates on Surgical Management - Pasquale Plateroti; Andrea Maria Plateroti; Solmaz Abdolrahimzadeh; Gianluca Scuderi (Journal of Ophthalmology)
Pseudoexfoliation syndrome (PES) is a systemic disorder caused by progressive accumulation of extracellular material over various tissues. PES usually determines increased intraocular pressure, changes in the anatomical aspects of the optic nerve, and visual field alterations leading to the diagnosis of pseudoexfoliation glaucoma (PEG). Use of topical medical treatment usually leads to poor results in terms of long-term follow-up but many surgical techniques, such as Argon Laser or Selective Laser Trabeculoplasty, have been proposed for the management of PEG affected patients. The present paper is a review on the pseudoexfoliation syndrome and pseudoexfoliation glaucoma with an update on surgical management.